(untitled) (Clinics, 2015)
OBJECTIVES: Remote ischemic perconditioning is the newest technique used to lessen ischemia/reperfusion injury. However, its effect in hypertensive animals has not been investigated. This study aimed to examine the effect of remote ischemic perconditioning in spontaneously hypertensive rats and determine whether chronic treatment with Olmesartan could influence the effect of remote ischemic perconditioning. METHODS: Sixty rats were randomly divided into six groups: vehicle-sham, vehicle-ischemia/reperfusion injury, vehicle-remote ischemic perconditioning, olmesartan-sham, olmesartan-ischemia/reperfusion and olmesartan-remote ischemic perconditioning. The left ventricular mass index, creatine kinase concentration, infarct size, arrhythmia scores, HIF-1α mRNA expression, miR-21 expression and miR-210 expression were measured. RESULTS: Olmesartan significantly reduced the left ventricular mass index, decreased the creatine kinase concentration, limited the infarct size and reduced the arrhythmia score. The infarct size, creatine kinase concentration and arrhythmia score during reperfusion were similar for the vehicle-ischemia/reperfusion group and vehicle-remote ischemic perconditioning group. However, these values were significantly decreased in the olmesartan-remote ischemic perconditioning group compared to the olmesartan-ischemia/reperfusion injury group. HIF-1α, miR-21 and miR-210 expression were markedly down-regulated in the Olmesartan-sham group compared to the vehicle-sham group and significantly up-regulated in the olmesartan-remote ischemic perconditioning group compared to the olmesartan-ischemia/reperfusion injury group. CONCLUSION: The results indicate that (1) the protective effect of remote ischemic perconditioning is lost in vehicle-treated rats and that chronic treatment with Olmesartan restores the protective effect of remote ischemic perconditioning; (2) chronic treatment with Olmesartan down-regulates HIF-1α, miR-21 and miR-210 expression and reduces hypertrophy, thereby limiting ischemia/reperfusion injury; and (3) recovery of the protective effect of remote ischemic perconditioning is related to the up-regulation of HIF-1α, miR-21 and miR-210 expression.